2015
DOI: 10.1159/000381193
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sodium Levels and Patient Outcomes in an Ambulatory Clinic-Based Chronic Kidney Disease Cohort

Abstract: Background: Chronic kidney disease (CKD) patients are prone to both hypo- and hypernatremia. Little has been published on the epidemiology of hypo- and hypernatremia in ambulatory patients with non-dialysis CKD. Methods: Data collected in two contemporaneous CKD cohort studies, the Renal Research Institute (RRI)-CKD study (n = 834) and the Study of Treatment of Renal Insufficiency: Data and Evaluation (STRIDE) (n = 1,348) were combined and analyzed to study the association between serum sodium (Na+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 45 publications
5
27
0
1
Order By: Relevance
“…CKD is another cause of hypervolaemic hyponatraemia, with a prevalence of 6% in non-dialysis CKD patients [25]. CKD accounted for 6% of our cases.…”
Section: Discussionmentioning
confidence: 81%
“…CKD is another cause of hypervolaemic hyponatraemia, with a prevalence of 6% in non-dialysis CKD patients [25]. CKD accounted for 6% of our cases.…”
Section: Discussionmentioning
confidence: 81%
“…1 ). Thus, seven studies 9 14 , 19 that comprised of 742,979 CKD patients were included in the meta-analysis. Table 1 presents the baseline characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 presents the baseline characteristics of the included studies. Among the seven articles, four studies 9 , 11 , 14 , 19 were limited to non-dialysis CKD patients, two studies 10 , 12 enrolled hemodialysis patients, and one study 13 included peritoneal dialysis patients. Furthermore, five studies 9 , 10 , 12 14 were conducted in the United States, Korea 19 and the United Kingdom 11 , in which each country contributed one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include changes of urine dilution and concentration in response to antidiuretic hormone, and alteration of water and Na and CI reabsorption and excretion 13,14 . Previous studies have reported that dysnatremias and hypochloremia are associated factors for mortality in patients with chronic kidney disease (CKD), with or without dialysis [15][16][17][18][19][20][21][22] . Thus, dyschloremias and dysnatremias have been proposed as potential useful factors for mortality prediction in this population [15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%